The Development of Psoriatic Arthritis in Patients With Psoriasis Is Preceded by a Period of Nonspecific Musculoskeletal Symptoms: A Prospective Cohort Study. Issue 3 (27th February 2017) - Eder, Lihi; Polachek, Ari; Rosen, Cheryl F.; Chandran, Vinod; Cook, Richard; Gladman, Dafna D.
Abstract : Objective: To assess whether the presence of nonspecific musculoskeletal symptoms, their degree, and change over time predict the development of psoriatic arthritis (PsA) in a prospective cohort of psoriasis patients without arthritis at baseline. Methods: This prospective cohort study involved patients with psoriasis who were assessed at baseline to exclude the presence of clinical PsA. The study participants were reassessed annually to determine if they had developed PsA. The presence of musculoskeletal symptoms and the patients' assessments of pain, fatigue, stiffness, physical function, and psychological distress were recorded at each visit. Cox proportional hazards models were used to assess what symptoms predicted the development of PsA. Results: A total of 57 of 410 psoriasis patients developed PsA. At baseline, the presence of arthralgia in women (hazard ratio [HR] 2.59, P = 0.02), heel pain (HR 4.18, P = 0.02), high fatigue score (HR 2.36, P = 0.007), and high stiffness score (HR 2.03, P = 0.045) predicted subsequent development of PsA. In addition, an increase from baseline in fatigue score (HR 1.27, P = 0.001), pain score (HR 1.34, P < 0.001), and stiffness score (HR 1.21, P = 0.03), and a worsening in physical function score (HR 0.96, P = 0.04) predicted the development of PsA. Conclusion: A preclinical phase exists in patients with PsA prior to the diagnosis of the disease. This phase is characterized by nonspecific musculoskeletal symptoms, including joint pain, fatigue, and stiffness.